Investigation of emotions management skills, perceived social competence, friendship quality, social exclusion and need to belong in adolescents - SERT, MERAL (E D P SCIENCES, 2018)
The research was conducted to investigate the dynamics between emotional management skills, perceived social competence, friendship quality, social exclusion, and need to belong in adolescents. Previous studies emphasize the importance of competencies in adolescents related to emotional management skills in social and academic life as well as in the family. In this context, emotional management skills gain an importance as a feature that can help adolescents become a member of a group and meet the need to belong by positively changing the perception of the social competence of the individual, increasing social harmony, and developing meaningful and supportive friendships. Research data was obtained by applying Emotions Management Skills Scale, Perceived Social Competence Scale, Friendship Quality Scale, Social Exclusion Scale, Need to Belong Scale and Personal Information Form on 431 students (195 male, 236 female) in 9th, 10th, and 11th Grades in Kadikoy district, Istanbul province. Significant differences were found in friendship quality, perceived social competence, and emotions management with respect to gender. In addition, differences were found in investigated characteristics with respect to age, grade, academic achievement, family dynamics and, a negative relationship was found between social exclusion and emotions management skills, perceived social competence, and friendship quality.
Keywords: Adolescence Period; Emotions Management Skills; Perceived Social Competence; Social Exclusion; Friendship Quality; Need to Belong; SELF-EFFICACY BELIEFS; PERCEPTIONS; REACTIVITY; ENGAGEMENT; CONTEXT